The Runaway Bride - Chukwuemeka, Ernest (Evans Brothers (Nigeria Publishers) Ltd, 2012)
The Runaway Bride is a play which narrates the ordeals of young teenage girls given out in early marriage$1! =s
Keywords: Plays